About Genesis of Collective Subjectivity in The Activity of Technological Club (to The Research Program) - Y.V. Gromyko; A.A. Ustilovskaya (Moscow State University of Psychology and Education, 2023)
The paper presents the results of studying the activities of technology clubs operating in different regions of Russia. Based on the materials of the All-Russian competition of technological clubs, the objectives, content and forms of organization of activities, the team of the circle, history and traditions, the nature of the interaction of participants and some other issues were analyzed. The characteristics of activity common to technological clubs are highlighted and illustrative examples are given. The concept of “joint consciousness of the club team” is introduced to describe a phenomenon that manifests itself in most effectively working technological clubs. From the point of view of the authors, the presence of a joint consciousness of the members of the club simultaneously affects the development of each participant and the group as a whole. Joint consciousness is a prerequisite for the formation of collective subjectivity. The collective subjectivity that arises in the understanding and reflection of the members of the circle club, in turn, changes the form of the organization of consciousness, in which ideal elements shred between all members of the club appear – goals, values, means of organizing joint activities, tasks to be solved. The authors of the article propose a program for further research of the phenomenon of joint consciousness as the basis of the shared membership in the club and the process of the emergence of collective subjectivity.